To the knowledge of the solitary vespid wasps (Hymenoptera: Vespidae: Masarinae and Eumeninae s. l.) of Uzbekistan - Fateryga, Alexander V.; Proshchalykin, Maxim Yu.; Mokrousov, Mikhail V.; Akhmedov, Askar G. (Zootaxa, 2023)
The knowledge of the solitary Vespidae of Uzbekistan is very poor and a preliminary list of species is provided. The list contains 105 species of 34 genera: seven species of three genera in the subfamily Masarinae, 96 species of 29 genera in Eumeninae s. str., one species in Raphiglossinae and one in Zethinae. Among them, eight genera and 27 species are reported from Uzbekistan for the first time; their label data and general distribution are reported. New synonymies are proposed: Leptochilus (Lionotulus Blüthgen, 1938) = L. (Neoleptochilus Blüthgen, 1961), syn. nov. = L. (Sarochilus Gusenleitner, 1970), syn. nov.; Leptochilus (Lionotulus) crassiceps (Kostylev, 1940) = L. (L.) flavicornis Giordani Soika, 1970, syn. nov.; Euodynerus (Pareuodynerus) cylindriventris (Kostylev, 1935) = E. (P.) distinctus (Kostylev, 1935), syn. nov.; Eustenancistrocerus (Eustenancistrocerus) askhabadensis (Radoszkowski, 1886) = E. (E.) jerichoensis (von Schulthess, 1928), syn. nov. = E. (E.) askhabadensis danticoides (Giordani Soika, 1943), syn. nov. = E. (E.) jerichoensis iconius Blüthgen, 1957, syn. nov. The synonymy of Eumenes (Eumenes) sareptanus André, 1884 with E. (E.) crimensis Blüthgen, 1938 is rejected. A nest of Stenodynerus chitgarensis Giordani Soika, 1970 is briefly described for the first time; it consisted of a constructed mud cell, with a turret-like entrance, attached to a subvertical surface of a stone. Bionomical observations on some other species are reported including prey records for three species, flower-visiting records for nine species, a sleeping aggregation of two species, and a Strepsiptera parasite of one species.